Economic effects of creditors' rights protection - Lekpek Ahmedin (Faculty of Law, Niš, 2021)
The willingness of creditors to satisfy the credit demand of the population and the economy under mutually acceptable conditions directly depends on the degree of legal protection enjoyed by creditors. In this paper, we deal with the protection of creditors' rights and the instruments used for this purpose. The aim of this paper is to consider the economic effects arising as a result of the application of instruments of creditors' rights protection, which affect not only the financial position of creditors and debtors but also the stability and efficiency of the financial and economic system as a whole. The research results show that the existence of an adequate level of protection of creditors' rights has a strong positive impact on the size and activity of the credit market. On the other hand, the application of various instruments of creditors' rights protection can cause both positive and negative effects on the creditors position. Yet, an excessively high level of creditors' protection can significantly worsen the position of debtors and, consequently, aggravate the position of creditors in the long run.